A Study on Urban Furniture: Nicosia Old City - Bolkaner, Mine Kuset; İnançoğlu, Selda; Asilsoy, Buket (European Journal of Sustainable Development, 2019)
Urban furniture can be defined as aesthetics and comfort elements that reflect the identity of a city and enable the urban space to become livable. Urban furniture is an important element of the city in order to improve the quality of urban life, to create a comfortable and reliable environment and to meet the needs of the users in the best way. For designing these elements, the social, economic, cultural and architectural structure of the city should be considered and evaluated. It is important to adapt the urban furniture to the urban texture and to the cultural structure achieving an urban identity, in order to ensure the survival and sustainability of the historical environments. In this study, a study was carried out in the context of urban furniture in Nicosia Walled City, which has many architectural cultures with its historical texture. In this context, firstly the concept of urban identity and urban furniture was explained and then, information about urban furniture was given in historical circles with urban furniture samples from different countries. As a field study, a main axis was determined and the streets and squares on this axis were discussed. These areas have been explored starting from Kyrenia Gate in North Nicosia; ?nönü Square, Girne Street, Atatürk Square, Arasta Square, Lokmac? Barricade and on the south side Ledra Street and Eleftherias Square. In this context, the existing furniture in the North and South were determined and evaluated in terms of urban identity accordingly. As a result, it can be suggested that the existing street furniture equipments, especially on the north side, do not have any characteristic to emphasize the urban identity. According to the findings, it was determined that the urban furniture in the streets and squares on the north side is generally older and neglected, and does not provide a unity with the environment, whereas on the south side, these elements on the street and square are relatively new, functional and environmentally compatible. Key words: urban furniture, historical environment, urban identity, Nicosia Old City